REFORMS IN IMPROVING THE QUALITY OF HIGHER EDUCATION AND ITS PHILOSOPHICAL AND LEGAL BASIS - Saparboevna, Jumaniyozova Nasiba (International Journal of Psychosocial Rehabilitation, 2020)
–The article analyzes the reforms in the higher education system in Uzbekistan in recent years, a system of measures aimed at improving the quality of higher education. The article also examines the issues of further improving the system of training highly qualified personnel, the introduction of advanced modern technologies in the process of radical reform and modernization of the education system, the conceptual aspects of innovative educational processes.